2022
DOI: 10.31222/osf.io/nf6mq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Hypothesis Reporting in Psychology: Comparing Preregistrations and Corresponding Publications

Abstract: This study assesses the extent of selective hypothesis reporting in psychological research by comparing the hypotheses found in a set of 459 preregistrations to the hypotheses found in the corresponding papers. We found that more than half of the preregistered studies we assessed contain omitted hypotheses (N = 224; 52.2%) or added hypotheses (N = 227; 56.8%), and about one-fifth of studies contain changed hypotheses (N = 82; 19%). We found only a small number of studies with demoted hypotheses (N = 2; 1%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…All the methods used in this thesis have been put in place, to the best of my knowledge, to protect against false positives. There is no doubt that more methodological work is still needed, as it has already been shown that solutions, such as pre-registrations, might not be the solution to all problems (Van den Akker et al, 2022). Nonetheless, the results from Paper I in this thesis show that pre-registration is an important step, as it binds the researcher not to do multiple testing.…”
Section: A Note To Further Researchmentioning
confidence: 84%
See 1 more Smart Citation
“…All the methods used in this thesis have been put in place, to the best of my knowledge, to protect against false positives. There is no doubt that more methodological work is still needed, as it has already been shown that solutions, such as pre-registrations, might not be the solution to all problems (Van den Akker et al, 2022). Nonetheless, the results from Paper I in this thesis show that pre-registration is an important step, as it binds the researcher not to do multiple testing.…”
Section: A Note To Further Researchmentioning
confidence: 84%
“…There has been some debate over the use of these pre-registration plans (Pham & Oh, 2021), but there seems to be an overall movement toward using these more (Simmons et al, 2021). It is, however, important to keep discussing these methods, as the first generation of pre-registered analysis still seems to contain errors (Claesen et al, 2021), and even in some cases, there was a massive difference between the published article and the preregistration ( Van den Akker et al, 2022).…”
Section: Solutions To the Issuementioning
confidence: 99%
“…Ideally, a preregistration provides a detailed overview of all planned analysis steps that can be referenced in a publication to clearly distinguish confirmatory from exploratory analyses [20]. However, analysis plans laid out in preregistrations are often vague, analyses are quietly changed or incompletely reported in publications, and sometimes preregistrations are even written retrospectively [109][110][111]. All these aspects clearly limit the value of preregistrations in practice and spawned the development of registered reports.…”
Section: Preregistration and Registered Reportsmentioning
confidence: 99%
“…There have been recommendations for simpler hypotheses in psychology to avoid misinterpretations and misspecifications [15]. Finally, several evaluations of preregistration practices have found that a significant proportion of articles do not abide by their stated hypothesis or add additional hypotheses [11,[16][17][18]. In sum, while multiple efforts exist to improve scientific practice, our hypothesis-making could improve.…”
Section: Introductionmentioning
confidence: 99%
“…We consider this useful and timely as, with preregistrations becoming more frequent, the hypothesis-making process is now open and explicit. However, preregistrations are difficult to write [19], and preregistered articles can change or omit hypotheses [11] or they are vague and certain degrees of freedom hard to control for [16][17][18]. One suggestion has been to do less confirmatory research [7,20].…”
Section: Introductionmentioning
confidence: 99%